ORELLANA CASTRO,GRACE LISBETH(2023)RESPUESTA ZOOTÉCNICA, NUTRICIONAL Y BIOQUÍMICA SÉRICA EN JUVENILES DE TILAPIA ROJA (Oreochromis mossambicus X Oreochromis niloticus) CON INCLUSIÓN DE SILICIO ORGÁNICO EN DIETA.Quevedo.UTEQ.78pag - ORELLANA CASTRO, GRACE LISBETH (2023)
The research was carried out in the aquaculture laboratory of the “La María” Campus for eight weeks with the objective of evaluating the zootechnical, nutritional and serum biochemical response in juvenile red tilapia with the inclusion of organic silicon in the diet, using a completely randomized design ( DCA), with six treatments: T1 (0mg), T2 (0.00125mg), T3 (0.0025mg), T4 (0.005mg), T5 (0.01mg) and T6 (0.05mg) of organic silicon and three repetitions (plastic aquariums ) with 15 fish (experimental unit) a total of 270 fish under study. Various variables were evaluated: zootechnical, nutritional and serum biochemical. The average initial weight and length of the tilapia juveniles were 7.49g to 7.51g and 8.39 cm to 8.32 cm, respectively, with statistical differences in the final weight and length of 29.11g and 13.39cm, the best size gain was 5.10cm (T6) with a specific growth rate of 2.42%. T2 presented a survival of 73.33% with a mortality of 26.67%, while the other treatments reached 100% survival. In nutritional parameters there were significant statistical differences (p>0.05), the best feed conversion (1.27%) and feed efficiency greater than 0.58% were observed in T6. The protein efficiency rate did not present significant differences with a value of 1.69%. Furthermore, T6 presented the highest glucose value of 79.00 mg/dL. In T2, a higher average of 77.33±2.52 mg/dL of cholesterol was obtained, the lowest level of triglycerides was 187.00 mg/dL with T3, concluding that the inclusion of organic silicon has positive effects on the zootechnical and nutritional parameters in the animals juvenile red tilapia.